Communication of organisational changes to employees: a case study. - Folose, Nkululeko Gladstone Victor. (My University, 1995)
The democratisation of local governmsnt requires effective communication structures. The current methods of communicating changes and developments to employees of the Sebokeng Town Council are: top management discussions, notice-boards and informing those affected. Their ineffectiveness is shown by the poor knowledge of local government issues revealed in a council characterised by adversarial union-management relations. Management appears to play a minimal role whilst shopstewards dominate the process of communicatlng changes to employees and the grapevine is said to provide information most timeously. The quest for change and for a two-way cornmunlcatlon process were endorsed strongly. Consultative meetings, discussions involving union representatives and informal worker discussions are the preferred methods of communication. It is recommended that a change management process be triggered by the researcher facilitating a more inclusive management-employee workshop to discuss the findings, establish an internal communications structure and explain how to disseminate information through briefing groups.
A research report submitted to the faculty of Management, University of the Witwatersrand in partial fulfilment of the requirements for the degree of Master of Management (in the field of Public and Development Management)
Keywords: Communication in organizations -- South Africa.; Organizational change -- South Africa.; Local government -- South Africa.